PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI PADA MATERI SALING KETERGANTUNGAN DALAM EKOSISTEM SISWA KELAS VII A SMP NEGERI 2 TANDUN TAHUN 2016 - Megawati Megawati (Indonesian Journal of Basic Education, 2018)
This action research generally aims to improve the results of Biology learning on the material of interdependence in ecosystems through the application of guided inquiry learning models for grade VII A students of SMP Negeri 2 Tandun. The data in this study were collected using tests, student observation sheets, teacher observation sheets, and field notes. This type of research is classroom action research. The research procedure consists of planning, implementation, observation and reflection. The results revealed that the initial test results showed that the absorption of students in the first cycle of meeting 1 was 68.57% (sufficient category) and cycle I meeting 2 was 68.6 (Enough) so the average cycle I (67.6) while cycle II meeting 1 is 72.71% (sufficient category) and cycle II meeting 2 is 78.71 (good category) to be cycle II average (86.35). For individual learning completeness in cycle I (50.00%) and cycle II 83.34 (good category). Based on the research conducted, it was concluded that the guided inquiry learning model could improve Biology learning outcomes for Grade VII A students at State Junior High School 2 Tandun